1997
DOI: 10.1002/(sici)1096-9071(199709)53:1<51::aid-jmv9>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Puumala and Dobrava viruses cause hemorrhagic fever with renal syndrome in Bosnia-Herzegovina: Evidence of highly cross-neutralizing antibody responses in early patient sera

Abstract: Hantavirus infection was diagnosed serologically by mu-capture IgM and IgG ELISAs in hemorrhagic fever with renal syndrome (HFRS) patients admitted to Tuzla Hospital, Bosnia-Herzegovina. The results indicated that more than one hantavirus caused the outbreak. To address the question of which hantavirus serotypes were involved, sequentially drawn sera were analyzed by focus reduction neutralization test (FRNT) for antibodies against Puumala, Hantaan, Dobrava, and Seoul hantaviruses. The data revealed that acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(86 citation statements)
references
References 36 publications
2
83
0
1
Order By: Relevance
“…An 80% reduction of the number of foci, as compared with the virus control, was used as a criterion for virus neutralisation titres and the titrations were performed as described earlier [30] (online Supplementary Material). Serum samples collected in January 2013 from two HFRS patients (Cherwell and Wrexham) were also tested using specific hantavirus FRNTs against SEOV, DOBV, PUUV and HTNV.…”
Section: Serologymentioning
confidence: 99%
“…An 80% reduction of the number of foci, as compared with the virus control, was used as a criterion for virus neutralisation titres and the titrations were performed as described earlier [30] (online Supplementary Material). Serum samples collected in January 2013 from two HFRS patients (Cherwell and Wrexham) were also tested using specific hantavirus FRNTs against SEOV, DOBV, PUUV and HTNV.…”
Section: Serologymentioning
confidence: 99%
“…2 An association of DOB virus with HFRS was recently found in patients from southeastern Europe (Albania, Greece, former Yugoslavia) and Russia. [5][6][7] In a study performed in Estonia (northeastern Europe), Plyusnin and others 8 demonstrated the presence of DOB virus in A. agrarius, the natural host of HTN virus in Asia. 1,2 In Slovakia (central Europe), HFRS is a well-known disease; clinical cases as well as infected rodents have been serologically diagnosed using HTN or PUU virus antigens.…”
mentioning
confidence: 99%
“…The focus reduction neutralization tests (FRNT) were performed on seropositive samples at the Swedish Institute for Communicable Dis- (12), and DOBV Slovenia strain (13) were used for FRNT analyses. The tests were performed as previously described by Lundkvist et al (14). In this protocol, the ELISA and/or immunoblotting seropositive samples were serially diluted and mixed with an equal volume of diluted virus, containing 30-70 focus forming units/100 ml.…”
Section: Methodsmentioning
confidence: 99%